Geochronology and Petrogenesis of the Gol Mod Massif: Implications for the Geodynamic Evolution of the Orkhon-Selenge Belt, Northwestern Mongolia - Odgerel, Dashdorjgochoo; Ganbat, Bayaraa; Antipin, Viktor; Sanchir, Dorjgochoo; Tumurchudur, Choinbol (Mongolian Geoscientist, 2022)
The Orkhon-Selenge Belt is a Late Permian to Early Triassic volcanic plutonic belt located in northern Mongolia and is part of the Central Asian Orogenic Belt. The Selenge Complex, which is a part of the Orkhon-Selenge Belt, is a key area for studying the tectonic and magmatic evolution of the Central Asian Orogenic Belt. This study aims to contribute to understanding of the geodynamic evolution of the Orkhon-Selenge Belt by investigating the petrology, geochemistry and geochronology of the rocks in the region. Our results indicate that intrusive rocks were characterized as high-K, Calc-alkaline series and metaluminous to weakly peraluminous I-type granite affinities and their geochemical characteristics are indicating as arc-like geochemical signatures with depleted in elements such as Nb, Ta, Ti and Y and enriched in elements such as Rb, Cs, Th, K and light rare earth elements. Using zircon U-Pb dating, we determined an age of 257.3±0.73 Ma for the alkali granite, suggesting that south-western part of the Orkhon-Selenge Belt formed during the Late Permian time. The Selenge pluton, which is closely related to Erdenet-Ovoo porphyry type mineralization, is a composite intrusion. However, the zircon grains display magmatic and low oxygen fugacity conditions, which characteristics are likely the effect of weak mineralization of magma ascent with Late Permian tectonothermal event in the south-west part of the Orkhon-Selenge Belt. The results of this study will provide insights into the formation and evolution of the north-western segment of the Mongol-Okhotsk Belt, and will have implications for our understanding of the tectonic history of this region.